(3eMGSHI GdefTBJ GdNGUI (B:s (3GdaQhY h GdGbSGe (B/s - (3GdTfWj, Gjefs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2008)
(3GdeMGjHI GdNGUI , eMGSHI GdLeYjGJ h GdfhGOj , eMGjHI GdafGOb , Gdegf GdMQI , eMGSHI GdebGhdGJ , eMGSHI GdeSJTajGJ , eMGSHI TQcGJ Gdfbd GdHMQj (B.s
(3eQGLY U(B.128s
Keywords: (3GdbWGY GdNGUs; (3GdeMGSHIs; (3eMGSHI GdTQcGJs